A Review of NAFLD Remission Strategies: From Molecular Mechanisms to Clinical Interventions - Chen, Weiyu (Exploring Science Academic Conference Series, 2026)
Nonalcoholic fatty liver disease (NAFLD) is a liver disease closely associated with insulin resistance and metabolic dysregulation. As a chronic disease for which no curative treatment is currently available, how to alleviate patients’ symptom s has become an important research topic. NAFLD affects a broad population worldwide, with a global prevalence exceeding 32.4% and reaching as high as 43.9% in China. To summarize strategies for symptom relief, this review systematically examines the remission approaches for NAFLD and extracts methods from four dimensions based on the existing literature, namely molecular mechanisms, lifestyle interventions, pharmacological therapy, and external therapies of traditional Chinese medicine. The findings indica te that ferroptosis, as a key mechanism in NAFLD progression, regulates lipid peroxidation and iron metabolism through the System xc⁻ –GSH–GPX4 pathway, providing new insights for targeted therapy. In terms of lifestyle intervention, ≥150 minutes of moderate -intensity aerobic exercise per week combined with resistance training can significantly reduce hepatic fat fraction, while the Mediterranean diet improves hepatic steatosis through antioxidant, anti -inflammatory, and gut microbiota -modulating effects, sh owing superiority over the ketogenic diet. Regarding pharmacological therapy, GLP -1 receptor agonists (GLP-1RAs) such as semaglutide have demonstrated significant improvement in steatosis in phase III trials, whereas ferroptosis inhibitors, although effective in animal models, still lack sufficient clinical translational data and require further validation. Traditional external therapies of Chinese medicine, such as Baduanjin and acupoint catgut embedding, show unique advantages in improving liver function and metabolic indicators; however, more standardized clinical optimization is required before large -scale promotion. Overall, future research in this field should focus more on multi -omics integrative analysis, the clinical translation of ferroptosis -targeted drugs, and the optimization of integrated traditional Chinese and Western medicine treatment strategies.